The Influence of HR Analytics, Development Competence and Leadership Support on Employee Performance with Organizational Agility as a Moderating Variable : (A Study on Employees of the Department of Industry and an Trade in Lampung Province) - Danti Indriana; Rahyono Rahyono; Reza Hardian Pratama (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the effect of HR Analytics, competency development, and leadership support on employee performance with organizational agility as a moderating variable among employees of the Department of Industry and Trade of Lampung Province. This research employed a quantitative approach by distributing questionnaires and analyzing the data using SEM-PLS. The results show that competency development and leadership support have a positive and significant effect on employee performance, while HR Analytics has no significant effect. Organizational agility does not moderate the relationship between HR Analytics, competency development, leadership support, and employee performance. These findings suggest that while HR Analytics may not directly influence performance, the development of competencies and strong leadership support remain critical to enhancing employee outcomes. Furthermore, the lack of a moderating effect from organizational agility indicates that factors beyond agility, such as employee training programs and leadership practices, play a more crucial role in driving performance. This study highlights the importance of strengthening employee competencies and leadership support to improve employee performance in government institutions. Further research could explore other potential moderating factors in this context.